2018
DOI: 10.14295/oh.v24i2.1174
|View full text |Cite
|
Sign up to set email alerts
|

Duração do ciclo e danos por altas e baixas temperaturas em gladíolo em função da época de plantio

Abstract: The planting date is an important factor affecting the developmental cycle and quality of final product. Indications from the literature are that gladiolus is a species that can be cultivated throughout the year, but in some periods, adverse conditions may occur, reducing the quality of the flower. Two field experiments (Experiment 1: August 2011 to July 2012 and Experiment 2: August 2012 to July 2013) were conducted in Santa Maria, RS, Brazil, to quantify the influence of planting dates on the duration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 7 publications
(11 reference statements)
1
14
0
1
Order By: Relevance
“…When planted in early dates, that occurs lower air temperatures (July and August), the cycle duration is extended for all cultivars, independent the cycle. This result was also found by Schwab et al (2018), which identified a change in the cycle duration when the planting was carried out in colder months, being prolonged when compared to those grown in the warmer months. The best planting date for these sites is during the second fortnight of July and first fortnight of August for presenting the best stems quality for three sites, because none of the cultivation sites was highlighted in relation to the quality stems.…”
Section: Resultssupporting
confidence: 71%
“…When planted in early dates, that occurs lower air temperatures (July and August), the cycle duration is extended for all cultivars, independent the cycle. This result was also found by Schwab et al (2018), which identified a change in the cycle duration when the planting was carried out in colder months, being prolonged when compared to those grown in the warmer months. The best planting date for these sites is during the second fortnight of July and first fortnight of August for presenting the best stems quality for three sites, because none of the cultivation sites was highlighted in relation to the quality stems.…”
Section: Resultssupporting
confidence: 71%
“…With respect to different developmental cycles of gladiolus, the tendency is that Late cultivars need to be planted earlier than Early cultivars to escape the occurrence of hightemperature damage during the reproductive period of the It is also noted that there will be a greater gap in production of gladiolus to meet certain seasons of the year in some regions such as Uruguaiana, Iraí, Santa Maria and Bagé, even if the less pessimistic scenario occurs (RCP2.6). To meet the demands during the hottest period of the year it will be necessary to develop techniques to reduce damage by high temperatures, like burned sepals (Schwab et al, 2018), such as more tolerant cultivars or the use of shading screens. The use of screens reduces the occurrence of sunburned peppers during the summer months in Southern Spain (López-Marin et al, 2011) and its effect on gladiolus crop still needs to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…If the minimum temperature is lower than or equal to −2 ºC during one day or if −2 ºC < T min < 3 ºC during four days in a row during the reproductive phase, then the floral stem is killed by frost. Heat injury in PhenoGlad is considered when the maximum temperature is greater than or equal to 34 ºC during three consecutive days during the reproductive phase, causing severe burning of sepals (Schwab et al, 2018). If the maximum temperature is higher than 48 ºC, the upper lethal temperature is reached, and the crop is killed by heat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the late summer and early autumn (February, March and April) is also a suitable period for the production of quality flower stems (Schwab et al, 2015b). In the RS, the demand for gladiolus has been increasing in different celebratory dates, such as Mother's Day, Women's Day and also for the ornamentation of interiors, parties and events (Schwab et al, 2018). These different forms of use as cut flowers are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%